2021
DOI: 10.1111/1365-2745.13592
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation and biodiversity–ecosystem function relationships in crop production systems and their role in sustainable farming

Abstract: We review the need for increasing agricultural sustainability, how this can in part be delivered by positive biodiversity–ecosystem function (BEF) effects, the role within these of plant–plant facilitation, and how a better understanding of this role may help to deliver sustainable crop (particularly arable) production systems. Major challenges facing intensive arable production include overall declines in biodiversity, poor soil structure and health, nutrient and soil particle run‐off, high greenhouse gas emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 116 publications
(126 reference statements)
1
39
0
Order By: Relevance
“…Shade avoidance can be maladaptive in wheat monocultures in terms of population yield [51] but adaptive in terms of community yield if the cropping system is diversified and plasticity aids optimal niche complementarity, e.g., in grassland species mixtures [52]. Hypothetically, this could hold true for crop species mixtures [53]. Consequently, genotypes such as Sel_L56 that might have increased shade avoidance and show high absolute early vigor in SL, SRL, leaf, and plant length might be promising in diversified cropping systems.…”
Section: Competetive Response Of Wheat and Competetive Effects On Mustardmentioning
confidence: 99%
“…Shade avoidance can be maladaptive in wheat monocultures in terms of population yield [51] but adaptive in terms of community yield if the cropping system is diversified and plasticity aids optimal niche complementarity, e.g., in grassland species mixtures [52]. Hypothetically, this could hold true for crop species mixtures [53]. Consequently, genotypes such as Sel_L56 that might have increased shade avoidance and show high absolute early vigor in SL, SRL, leaf, and plant length might be promising in diversified cropping systems.…”
Section: Competetive Response Of Wheat and Competetive Effects On Mustardmentioning
confidence: 99%
“…But, our results also illuminate elaborate root communication that forms adversarial or beneficial relationships with many other organisms in the pedosphere, and these relationships are crucial for sustaining health of the individuals and organizing communities; as well as the ecosystem as a whole [10,13,14,[32][33][34]. Our study adds to the burgeoning body of evidence illustrating how knowledge of the hidden half can be exploited to improve plant growth and productivity in managed production systems e.g., [6].…”
Section: Discussionmentioning
confidence: 52%
“…For example, Li et al [5] found that root exudates from Zea mays L. promoted Vicia faba L. nodulation and increased N 2 -fixation to increase Z. mays productivity when the two species were intercropped. Such biodiversity effects in modern cropping systems are supported by ancient origins and contemporary ecological research [6]. Other experimental and observational studies have advanced our understanding of how such root behavior contributes to the over-yielding that often accompanies biodiversity [4,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…While a single wheat genotype can be selected to poorly compete with its conspecifics in a monoculture stand, it is less clear what sort of interactions should be selected for among intercrop partners, particularly given the dynamic and inter-dependent nature of these interactions. An increasingly detailed description of favorable interaction effects is being compiled, although it remains context-, crop-, and experiment-specific in many cases ( Brooker et al, 2021 ). Efforts to generate in silico ideotypes are providing novel insights ( Louarn et al, 2020 ), but still require confirmation of their ability to predict as-yet unidentified traits with significant agronomic impact.…”
Section: Breeding Directions For Intercrop Performancementioning
confidence: 99%